Quantifying organic matter and functional groups in particulate matter filter samples from the southeastern United States – Part 2: Spatiotemporal trends - A. J. Boris (Atmospheric Measurement Techniques, 2021)
Organic species within atmospheric particles vary widely in molecular structure. The variety of molecules that comprise the aerosol make it rich in information about its sources and chemical life cycle but also make particulate organic matter (OM) difficult to characterize and quantify. In Part 1 of this pair of papers, we described a direct method for measuring the composition and concentrations of OM in aerosol samples that is compatible with routine monitoring of air quality. This method uses Fourier transform infrared (FT-IR) spectrometry of filter-based aerosol samples to quantify bonds, or functional groups, that represent the majority of organic composition. Summation of these functional groups gives OM. In this paper, functional group and OM concentrations are directly measured in 8 years of aerosol samples collected at two rural and two urban sites in the Southeastern Aerosol Research and Characterization (SEARCH) network. FT-IR spectrometry with a multivariate calibration is used to quantify the concentrations of aliphatic C−H (aCH), carboxylic acid (COOH), oxalate (oxOCO; representing carboxylates), non-acid and non-oxalate carbonyl (naCO), and alcohol O−H (aCOH) in approximately 3500 filter samples collected every third day from 2009 through 2016. In addition, measurements are made on samples from all days in 2016. To the best of our knowledge, this is the longest time period over which this type of analysis has been applied, and this work also demonstrates the application of a more chemically complete and less destructive method than in prior work using alternate techniques. A decline in the total OM is observed from 2011 to 2016 due to a decrease in the more oxygenated functional groups (carboxylic acid and oxalate) and is attributed to anthropogenic SO2 and/or volatile organic compound (VOC) emissions reductions. The trend in OM composition is consistent with those observed using more time- and labor-intensive analytical techniques. Concurrently, the fractional contributions of aCOH and naCO to OM increased, which might be linked to monoterpene-derived secondary OM, with plausible influences from decreasing NOx and/or increasing O3 concentrations. In addition, this work demonstrates that OM to organic carbon (OM/OC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="270fcfea4aa8da0a3890b37300b7cd9e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-14-4355-2021-ie00001.svg" width="42pt" height="14pt" src="amt-14-4355-2021-ie00001.png"/></svg:svg>) ratios in the southeastern US (SE US) did not appreciably change over the study time period as a result of these competing functional group contributions to OM. Monthly observations support the sources suggested by these overall trends, including evidence of strong biogenic and photo-oxidation influences. Daily samples from 2016 further elucidate the consistent impact of meteorology and biomass burning events on shorter-term OM variability, including prescribed burning in the winter or spring and wildfires in the autumn, although these sources did not appear to be strong contributors to long-term OM or composition trends in the SE US. These shorter-term and spatial observations reinforce the results of the broader dataset and serve to evaluate the applicability of FT-IR spectrometry measurement to trends analysis on various timescales relevant to routine monitoring of aerosol composition.